Effects of foliar application of Moringa leaf extract on deficit irrigation and tomato (Solanum lycopersicum L.) productivity - Agada, Odu Odo (2018)
Moringa oleifera leaf extract (MLE), known to contain various phytochemicals, has been documented to enhance drought tolerance in crops, presenting a competitive technology in reducing the effect of water stress, enhancing water use efficiency and reducing use of chemical enhancers in crop production. The present study was undertaken to examine the effects of MLE on deficit irrigation and productivity of tomato, Solanum lycopersicum, with the objective of enhancing productivity while augmenting water use efficiency. Conducted under a rain-sheltered facility on heat tolerant tomato variety MARDI MT1, treatments consisted of four levels of sustained deficit irrigation (SDI) computed as percentages of field capacity (FC) viz. 39, 53, 68 and 100 % FC, applied on plants growing in media maintained at soil water potential levels of 1351.08, 968.56, 618.76 and 33 KPa respectively, at 2 weeks after transplanting (WAT). Results showed that at 39 % FC, reductions over control included plant height (33.75 %), total leaf area (59.98 %), fruit weight (71 %), net photosynthesis (44 %) and leaf water potential (56 %). Yield water use efficiency (YWUE) showed a linear relationship between full (100 %) irrigation and lowest at 39 % FC. There was no significant difference between the control and the 68 % FC level on growth, fruit weight and water use efficiency, suggesting it as the appropriate SDI level. The study observed the effects of different concentrations of MLE on growth, yield and water use efficiency under 53 % SDI. Four concentrations of MLE (0, 2.2, 3.3 and 6.7 %) were applied weekly at the rate of 25 ml plant-1. The 6.7 % MLE treatment recorded maximum values for relative water content (RWC) (14.91 %), net photosynthesis (17.25 %), fruit weight (18.85 %) and YWUE (28.41 %) over control. MLE at 6.7 % was observed to be the optimum concentration for reducing negative effects of 53% SDI. The effects of seven timing schedules of MLE applications on productivity under SDI were evaluated and was observed that combination timing performed better than single application timing schedules. The control timing schedule gave significantly higher values for the following parameters: plant height, fruit yield, net photosynthesis and catalase enzyme activity. The control timing schedule produced 35.58, 17.46, 21.27, 17.4 and 14.58 % higher fruit weight than the vegetative, flowering, fruiting, vegetative and flowering, and flowering and fruiting timing schedules respectively. The triple combination timing schedule was therefore the optimum timing for MLE applications. In a comparative study, MLE and benzyl amino purine (BAP) were compared under similar conditions. The MLE recorded significant capacity in enhancing water stress tolerance compared to BAP, yielding higher values in fruit yield (21.52 %), Fv/Fm (16.44 %), total chlorophyll content (22.79 %), photosynthesis (11.97 %) and nutrient element accumulation. This suggests that MLE could be used as an alternative to BAP in enhancing growth and productivity. The study concluded that 6.7 % MLE, applied at the vegetative, flowering and fruiting combination timing schedules was the optimum condition for foliar application of MLE in reducing negative effects of SDI on tomato fruit yield and water use efficiency.